2019
DOI: 10.29359/bjhpa.11.1.0
|View full text |Cite
|
Sign up to set email alerts
|

Studies of kicking of three targets – does sex differentiate the velocity of the taekwondo front kick?

Abstract: Background:The aim of the research was to obtain knowledge concerning the impact of selected external determinants (kick target) and internal determinants (sex) on the movement kinematics during the performance of a front kick by taekwon-do practitioners. Material and methods:The analysis was performed on 8 men (18.3 ±1.7 years old) and 6 women (19.8 ±3.8 years old) practising taekwon-do. During research they performed front kicks into the air, at a table tennis ball hanging on a line and a training target (sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
(11 reference statements)
2
0
0
Order By: Relevance
“…The obtained results also correspond to the tendencies described in other groups of Polish students of teaching specialisations, including physical education, in which it was shown that the students from the University of Physical Education (AWF Kraków), similarly to the students of other specialisations, obtained the highest results in the area of positive mental attitude and less in the category of preventive behaviours (Kosiba et al, 2019b). Similar trends were also described among students of Poznań universities and the Holy Cross University in Kielce, who showed the highest intensity of behaviours associated with positive mental attitude, and less regarding preventive and rational eating behaviours (Rasińska, 2012;Palacz, 2014).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The obtained results also correspond to the tendencies described in other groups of Polish students of teaching specialisations, including physical education, in which it was shown that the students from the University of Physical Education (AWF Kraków), similarly to the students of other specialisations, obtained the highest results in the area of positive mental attitude and less in the category of preventive behaviours (Kosiba et al, 2019b). Similar trends were also described among students of Poznań universities and the Holy Cross University in Kielce, who showed the highest intensity of behaviours associated with positive mental attitude, and less regarding preventive and rational eating behaviours (Rasińska, 2012;Palacz, 2014).…”
Section: Discussionsupporting
confidence: 85%
“…The demonstrated high level of health-promoting behaviours in the domain of positive mental attitude and the so-called pro-health practices (including recreational physical activity) among physical education students may be associated with the educational profile of the studied group of academic youth oriented toward increased physical activity, which is an important factor contributing to the optimisation of mental state. Relatively high results in the so-called pro-health practices domain (including, but not limited to, physical activity) correspond, at the same time, to trends described in other studies, confirming a higher level of physical activity of physical education students compared to students with a different educational profile (Fagaras, Radu, Vanvu, 2015;Bednarek, Pomykała, Bigosińska, Szyguła, 2016;Yager, Gray, Curry, McLean, 2017;Kosiba, Gacek, Wojtowicz, Majer, 2019b). In another study, Spanish physical education students were also characterised by a more healthy lifestyle and more favourable body composition as well as blood lipid profile than students of other university specialisations, which is related to the educational profile focused on promoting an active and healthy lifestyle (Grima, Blay, 2016).…”
Section: Discussionsupporting
confidence: 78%